2009
DOI: 10.1210/me.2009-0120
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Receptor 30 Expression Is Up-Regulated by EGF and TGFα in Estrogen Receptor α-Positive Cancer Cells

Abstract: In the present study, we evaluated the regulation of G protein-coupled receptor (GPR)30 expression in estrogen receptor (ER)-positive endometrial, ovarian, and estrogen-sensitive, as well as tamoxifen-resistant breast cancer cells. We demonstrate that epidermal growth factor (EGF) and TGF alpha transactivate the GPR30 promoter and accordingly up-regulate GPR30 mRNA and protein levels only in endometrial and tamoxifen-resistant breast cancer cells. These effects exerted by EGF and TGF alpha were dependent on EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 73 publications
4
110
0
3
Order By: Relevance
“…involved in tumor aggressiveness such as hypoxia, in the proliferation and migration of breast cancer cells and CAFs (Albanito et al 2008, Vivacqua et al 2009, Recchia et al 2011. Likewise, estrogens have been shown to stimulate growth effects in tamoxifen-resistant breast cancer cells through both an increased expression of GPER1 and the GPER1-mediated transactivation of EGFR (Ignatov et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…involved in tumor aggressiveness such as hypoxia, in the proliferation and migration of breast cancer cells and CAFs (Albanito et al 2008, Vivacqua et al 2009, Recchia et al 2011. Likewise, estrogens have been shown to stimulate growth effects in tamoxifen-resistant breast cancer cells through both an increased expression of GPER1 and the GPER1-mediated transactivation of EGFR (Ignatov et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As regards the regulation of GPER1, our previous studies have shown that some important growth-factormediated transduction pathways such as EGFR (Albanito et al 2008, Vivacqua et al 2009) and IGF1 (Bartella et al 2012 are involved in the expression and function of GPER1 in cancer cells. Interestingly, high levels of expression of GPER1 in breast, endometrial, and ovarian tumors have been associated with a higher risk of developing metastatic disease and poor survival (Prossnitz & Barton 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that the activation of the Gα s protein by GPER is responsible for the estrogen, phyto-and xenoestrogens stimulation of adenylate cyclase and the ensuing increase in cAMP in breast cancer cells [140,141] . The signaling events upon GPER activation by both estrogens and notably ER antagonists can lead to gene transcription as well as to the growth and migration in diverse hormone-sensitive tumors like breast, endometrial and ovarian cancer [142][143][144][145][146][147][148][149] . Notably, GPER was also involved in the stimulatory effects elicited by estrogens and ER antagonists in cancer-associated fibroblasts [147,150] .…”
Section: Gpcrs Activated By Hormonesmentioning
confidence: 99%
“…In 2004 and 2005, two studies reported that 17-β-estradiol (E2) binds to and signals through GPR30 with high affinity and in vitro potency, respectively (5,6). GPR30 has been speculated to have a potentially important role in cancer progression, including breast, endometrial, prostate, ovarian and thyroid cancers (7)(8)(9)(10)(11)(12). A previous study, using a breast cancer patient specimen and cell model, showed that GPR30 signaling is involved in the development of endocrine therapy resistance (13,14).…”
Section: Introductionmentioning
confidence: 99%